Complex formation between RAS and RAF and other protein kinases. - Van Aelst, L (1993)
We used a Saccharomyces cerevisiae genetic system to detect the physical interaction of RAS and RAF oncoproteins. We also observed interaction between RAS and byr2, a protein kinase implicated as a mediator of the Schizosaccharomyces pombe ras1 protein. Interaction with RAS required only the N-terminal domains of RAF or byr2 and was disrupted by mutations in either the guanine nucleotide-binding or effector-loop domains of RAS. We observed interaction between MEK (a kinase that phosphorylates mitogen-activated protein kinases) and the catalytic domain of RAF. RAS and MEK also interacted but only when RAF was overexpressed.